Adolescent birth and child undernutrition: an analysis of demographic and health surveys in Bangladesh, 1996–2017. Issue 1 (14th May 2021) - Nguyen, Phuong Hong; Scott, Samuel; Khuong, Long Quynh; Pramanik, Priyanjana; Ahmed, Akhter; Rashid, Sabina Faiz; Afsana, Kaosar; Menon, Purnima
Abstract: Adolescent birth is a major global concern owing to its adverse effects on maternal and child health. We assessed trends in adolescent birth and examined its associations with child undernutrition in Bangladesh using data from seven rounds of Demographic and Health Surveys (1996–2017, n = 12, 006 primiparous women with living children <5 years old). Adolescent birth (10–19 years old) declined slowly, from 84% in 1996 to 71% in 2017. Compared with adult mothers (≥20 years old), young adolescent mothers (10–15 years old) were more likely to be underweight (+11 pp), have lower education (−24 pp), have less decision‐making power (−10 pp), live in poorer households (−0.9 SD) with poorer sanitation (−15 pp), and have poorer feeding practices (10 pp), and were less likely to access health and nutrition services (−3 to −24 pp). In multivariable regressions controlled for known determinants of child undernutrition, children born to adolescents had lower height‐for‐age Z‐scores (−0.29 SD for young and −0.10 SD for old adolescents (16–19 years old)), weight‐for‐age Z‐score (−0.18 and −0.06 SD, respectively) as well as higher stunting (5.9 pp) and underweight (6.0 pp) than those born to adults. In conclusion, birth during adolescence, a common occurrence in Bangladesh, is associated with child undernutrition. Policies and programs to address poverty and improve women's education can help delay marriage, reduce early childbearing, and improve child growth. Abstract : Adolescent birth is a major global concern owing to its adverse effects on maternal and child health. We assessed trends in adolescent birth and examined its associations with child undernutrition in Bangladesh using data from seven rounds of Demographic and Health Surveys. Our analysis demonstrates that birth during adolescence, a common occurrence in Bangladesh, is associated with child undernutrition.